Electrostatic analyzer design for solar wind proton measurements with high temporal, energy, and angular resolutions. Issue 2 (6th February 2017) - Cara, Antoine; Lavraud, Benoit; Fedorov, Andrei; De Keyser, Johan; DeMarco, Rossana; Marcucci, M. Federica; Valentini, Francesco; Servidio, Sergio; Bruno, Roberto
Abstract: We present the design study of an electrostatic analyzer that permits combined high temporal, energy, and angular resolution measurements of solar wind ions. The requirements for high temporal, energy, and angular resolutions, combined with the need for sufficient counting statistics, lead to an electrostatic analyzer with large radius (140 mm) and large geometric factor. The resulting high count rates require the use of channel electron multipliers (CEMs), instead of microchannel plates, to avoid saturation. The large radius further permits the placement of 32 CEM detectors at the analyzer focal plane, thereby providing very high angular resolution in azimuth (1.5°). Electrostatic simulations were performed to define the analyzer geometric factor, energy resolution, analyzer constant (K), elevation response, etc. Simulations were also performed to define the geometry of the deflectors and collimator that are used to provide the proper energy resolution, field of view, and angular resolution (1.5°) in elevation as well (the total field of view of the design is ±24° × ±24°). We show how this design permits unprecedented measurements of the fine structure of the solar wind proton beam and other important features such as temperature anisotropy. This design is used for the Cold Solar Wind instrument of the medium‐class Turbulent Heating ObserveR mission, currently in phase A at the European Space Agency. These unprecedented measurement capabilities are in accordance with and even beyond the requirements of the mission. Key Points: A new solar wind ion instrument design is presented Simulations are used to define a design with unprecedented temporal and angular resolutions A plasma turbulence simulation is used to show the measurement capabilities achieved